2022
DOI: 10.1039/d2nr04549d
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of Zn with submicron resolution and its conversion into Zn/ZnO core–shell structures

Abstract: Electrohydrodynamic redox 3D printing (EHD-RP) is an additive manufacturing (AM) technique with submicron resolution and multi-metal capabilities, offering the possibility to switch chemistry during deposition "on-the-fly". Despite the potential for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Our results demonstrate the deposition of metallic structures with EHD-RP from aqueous metal salt solutions with similar characteristics to those previously printed from sacrificial anodes 35,38,39 . The general advantage in the use of metal salts over sacrificial anodes is the increased range of printable metals, because no anodic dissolution must be guaranteed (which can be a challenge, as shown for the case of Zn 38 ) and soluble salts exist for a large variety of metals.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results demonstrate the deposition of metallic structures with EHD-RP from aqueous metal salt solutions with similar characteristics to those previously printed from sacrificial anodes 35,38,39 . The general advantage in the use of metal salts over sacrificial anodes is the increased range of printable metals, because no anodic dissolution must be guaranteed (which can be a challenge, as shown for the case of Zn 38 ) and soluble salts exist for a large variety of metals.…”
Section: Introductionsupporting
confidence: 80%
“…Intriguingly though, the previously reported deposition of Cu-Ag alloys by EHD-RP indicated that this technology can directly deposit alloys without the need of elaborate tailoring of the plating bath -potentially significantly simplifying alloying by electrochemical deposition. EHD-RP is based on a solvent-filled quartz nozzle (both, organic and aqueous solvents have been demonstrated 35,38 ) in close proximity (approx. 10 µm) to a conductive substrate.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this challenge of high geometric fidelity in EHD printing, we here develop a combined experimental and modeling approach to investigate the flight dynamics of charged droplets using electrohydrodynamic redox 3D printing (EHDRP) process as a model system. EHDRP has recently been introduced as an electrochemical alternative to EHD, 4,23 in which the nanoparticles suspension is replaced with metal ions in solution. This technique advantageously combines both the high deposition rate of EHD and the various benefits of EC-based nanoscale 3D printing, 24 including superior as-deposited materials quality, 25 tunable microstructures, [26][27][28] and no requirement for post-printing annealing steps.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this challenge of high geometric fidelity in EHD printing, we here develop a combined experimental and modeling approach to investigate the flight dynamics of charged droplets using the electrohydrodynamic redox 3D printing (EHD-RP) process as a model system. EHD-RP has recently been introduced as an electrochemical alternative to EHD, , in which the nanoparticle suspension is replaced with metal ions in solution. This technique advantageously combines both the high deposition rate of EHD and the various benefits of EC-based nanoscale 3D printing, including superior as-deposited material quality, tunable microstructures, and no requirement for postprinting annealing steps.…”
Section: Introductionmentioning
confidence: 99%